Comparing attitudes of organic and conventional farmers towards organic farming in Malaysia - Mohamed Haris, Nur Bahiah; Garrod, Guy; Gkartzios, Menelaos; Proctor, Amy (Faculty of Agriculture, Universiti Putra Malaysia, 2018)
Farmers’ attitude towards organic farming practices is crucial and should not be overlooked in shaping the potential of organic farmers in adopting these practices. Several studies highlights that farmers attitudes are becoming an important determinant in adopting new technologies, particularly to the organic farming (e.g., Burton et al., 2003; Altenbuchner et al., 2016; Okon & Idiong, 2016). As demand is significantly increasing each year, however, the adoption rate among Malaysian farmers is still very low and the number of certified farmers remain small (Tiraieyari, Hamzah, & Abu Samah, 2014). In fact, their knowledge and perceptions towards organic farming are also still lacking among farmers (Assis & Mohd Ismail, 2011), and this should not be overlooked. Therefore, this paper aims to compare farmers attitude that comprise of their environmental concern, profit orientation, risk averse and information seeking behaviour towards organic farming adoption. This study was carried out in all four regions of peninsular Malaysia including Northern, Central, Southern, and East Coast region. The findings has the potential to improve government intervention in promoting the adoption of organic farming and create awareness of the behaviour that might influence farmers’ to adopt organic farming for sustainable agriculture in the future.